Precautionary Saving and Income Uncertainty in Germany: New Evidence from Microdata - Nikolaus Bartzsch (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
The saving ratio of households in Germany has increased in the past few years when the income trend was weak. This could be due to precautionary saving. In this paper, the importance of precautionary saving against income uncertainty is analyzed empirically using micro data from the German Socio-Economic Panel Study (GSOEP). Wealth in 2002 is regressed on alternative measures of income uncertainty in a cross-section of households. In addition to the usual controls, risk aversion is also taken into account. When using net financial wealth, precautionary saving is statistically significant and economically quite important. The share of precautionary net financial wealth in total aggregate net financial wealth is on average about 20%. Compared with net financial wealth, housing wealth is not used as a buyer stock against income uncertainty, confirming the hypothesis that this kind of asset is rather illiquid.
Keywords: D91; E21; J24; 330; precautionary saving; precautionary wealth; buyer-stock model